2012
DOI: 10.1111/j.1582-4934.2012.01542.x
|View full text |Cite
|
Sign up to set email alerts
|

Genistein as a potential inducer of the anti‐atherogenic enzyme paraoxonase‐1: studies in cultured hepatocytes in vitro and in rat liver in vivo

Abstract: A number of cardioprotective effects, including the reduced oxidation of the low-density lipoprotein (LDL) particles, have been attributed to dietary soy isoflavones. Paraoxonase 1 (PON1), an enzyme mainly synthesized in the liver, may exhibit anti-atherogenic activity by protecting LDL from oxidation. Thus, dietary and pharmacological inducers of PON1 may decrease cardiovascular disease risk. Using a luciferase reporter gene assay we screened different flavonoids for their ability to induce PON1 in Huh7 hepat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 52 publications
0
19
0
2
Order By: Relevance
“…Unlike quercetin, catechin showed little effect on PON1 activity, despite the fact that catechins are known to be relatively potent free radical scavengers in vitro , indicating that the free radical scavenging properties of flavonoids in vitro do not seem to be positively associated with their PON1‐inducing activity. Among various dietary polyphenolic compounds, catechin was a poor inducer of PON1 mRNA and PON1 transactivation as indicated in studies …”
Section: Discussionmentioning
confidence: 91%
“…Unlike quercetin, catechin showed little effect on PON1 activity, despite the fact that catechins are known to be relatively potent free radical scavengers in vitro , indicating that the free radical scavenging properties of flavonoids in vitro do not seem to be positively associated with their PON1‐inducing activity. Among various dietary polyphenolic compounds, catechin was a poor inducer of PON1 mRNA and PON1 transactivation as indicated in studies …”
Section: Discussionmentioning
confidence: 91%
“…With this study, besides these known constituents, natto may contribute its biological functions via G7P, demonstrated to improve the oral absorption of genistein. Moreover, some in vivo studies reported that genistein failed to have a biological effect via oral administration (Naik et al, 1994;Schrader et al, 2012;Turner et al, 2013) perhaps because of insufficient plasma exposure of genistein in the tests. With an oral route, G7P may have more efficient biological functions than genistein on its own because of increasing plasma level of genistein.…”
Section: Discussionmentioning
confidence: 96%
“…For a beneficial health effect by an oral route, a relatively high dose of~40 to 50 mg daily is required (Dixon & Ferreira, 2002;Mortensen et al, 2009). Therefore, some in vivo studies with oral administration at a reasonable dosage showed that genistein failed to reduce postmenopausal bone loss and had no significant effect on cardiovascular diseases and cancer chemoprevention (Naik, Lehr, & Pienta, 1994;Schrader et al, 2012;Turner et al, 2013).…”
Section: Introductionmentioning
confidence: 97%
“…6 Endojen antioksidan bir enzim olan paraoxonase-1 (PON-1) karaciğerde hepatositlerde üretilmektedir. 7 İnsanda 7. kromozomun q21-22 bölgesinde lokalize paraoksonaz (PON) multigen ailesi, PON-1, PON-2 ve PON-3 diye isimlendirilen üç üyeden oluşmaktadır.…”
Section: Introductionunclassified